2022
DOI: 10.3389/fpsyg.2022.923626
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Differences in Psychological Distress Between Chinese Dentists and Dental Nurses

Abstract: BackgroundDoctors and allied health professionals are facing serious mental health issues, which have received widespread attention. This study aimed to explore the occupational differences in psychological distress between Chinese dentists and dental nurses.Materials and MethodsThe data was collected from a cross-sectional study conducted by the Chongqing Stomatological Association. Medical personnel involved in this survey were invited to complete a battery of self-administrated questionnaires, specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
2
6
1
Order By: Relevance
“…Low job satisfaction was found to be able to increase the risk of psychological distress after controlling the potential confounding factors, which is in line with the findings in a prior study (Zhang et al, 2022). Nurses' job satisfaction includes satisfaction from their working conditions, relationships with colleagues and managers, scheduling and staffing, salaries, promotion opportunities, job security, work time, and managers' acknowledgement of their performance (Spector, 1997).…”
Section: Discussionsupporting
confidence: 86%
“…Low job satisfaction was found to be able to increase the risk of psychological distress after controlling the potential confounding factors, which is in line with the findings in a prior study (Zhang et al, 2022). Nurses' job satisfaction includes satisfaction from their working conditions, relationships with colleagues and managers, scheduling and staffing, salaries, promotion opportunities, job security, work time, and managers' acknowledgement of their performance (Spector, 1997).…”
Section: Discussionsupporting
confidence: 86%
“…This finding is consistent with a study conducted in Qatar, which revealed age and experience as significant predictors of PPE compliance ( 38 ). It might be explained by the fact that dental professionals at this age tend to work longer hours per week than those older and have higher job and family stress than those younger ( 39 , 40 ). These factors could aggravate their job burnout and subsequently reduce their compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Dental nurses were somewhat satis ed with their jobs in Jordan (53.5%) (59) which contrasted with the ndings by Naidu, Gobin (66) in Trinidad, where unsatisfactory working conditions for dental nurses were reported. Additionally, studies in Israel and China showed that there was psychological distress in dental nurses which was linked to lower pay, longer workweeks, burnout, high job stress, lower job satisfaction, regret over career choice, and violent events in the hospital (19,62).…”
Section: Work Environmentmentioning
confidence: 99%
“…Remuneration, favourable working relationships and surroundings, training opportunities, and exible schedules should be considered to aid in both the retention and recruitment of dental nurses (16, 18). Dental nurses' psychological distress was in uenced by their age, lower pay, longer workweeks, burnout, high levels of stress and discontent at work, a lack of leisure time, and a subpar healthcare environment (19). Despite the evidence on the need for studies on dental nurses and their increased risk, globally, there is limited research on the well-being of dental nurses.…”
Section: Introductionmentioning
confidence: 99%